Tantangan dan Peluang dalam Pembelajaran IPS di Era Digital - Safitri Safitri; Putri Kasandra D; Muchti Inayah; Oman Farhurrahman (Aktivisme: Jurnal Ilmu Pendidikan, Politik dan Sosial Indonesia, 2025)
In the era of advancing technology, accessing information across various fields, including education, has become easier. The digital era demands that students adapt to technology to avoid falling behind in the face of rapid developments. This article employs a literature study method to analyze various theories and previous research relevant to the challenges and opportunities of learning Social Studies (IPS) in the digital era. In this context, both teachers and students need to possess strong digital literacy skills to filter accurate, objective, and useful information that supports the learning process.